Development of Social Interaction Teaching Modules to Improve Student Discipline at Community Learning Centers - Misbahudin Azhar; Dewi Liesnoor Setyowati; Hartati Sulistyo Rini; Martien Herna Susanti; Hamdan Tri Atmaja (Universitas Negeri Semarang, 2026)
This study responds to the persistent challenge of low learning discipline in non-formal social studies programs by developing and testing a module. This study aims to (1) analyze the implementation of the teaching module on social interaction that has been used so far, (2) develop a teaching module on social interaction based on the character value of discipline and assess the feasibility of the module, and (3) analyze the effectiveness of the module in improving student discipline. This study uses the Research and Development method with the ADDIE model. The research begins with a needs analysis through observation, interviews, and focus group discussions. The design and development stage produces a module based on the value of Discipline. The validity of the content and practicality are evaluated by two experts. The results show that the module is in the feasible to highly feasible category, requiring only minor technical revisions. The module was implemented for students. Effectiveness was tested through a single-group pretest-posttest design involving 30 students, using a Discipline questionnaire. The average discipline score increased from 25.00 (62.5% of the maximum score) to 30.33 (75.8%), and the difference was statistically significant at p = 0.001 (p < 0.05) with a moderate to large effect size. The study concluded that the module was effective in strengthening student discipline and contributed as a context-based character education resource for Community Learning Centers.